ASOSIASI ANTARA KEMAMPUAN GENERALISASI MATEMATIK DENGAN SELF-CONCEPT SISWA SMP YANG MENGGUNAKAN STRATEGI PEMBELAJARAN BERBASIS VBA MICROSOFT EXCEL - Citra Megiana Pertiwi; Risa Amelia Jayanti; Muhammad Afrilianto (IKIP Siliwangi, 2018)
The purpose of this research is to find the correlation between mathematical generalization skill and student’s self-concept in learning activities by using learning strategy based on VBA’s Microsoft Excel. Experimental method is used in the research with 2 different classes. The first class is given by VBA Microsoft Excel learning based, while the other class is given common learning method. In addition, the data sample used in this research are all Junior High School in Cimahi, one school is selected randomly and SMP Negeri 4 Cimahi has been selected. The Sample chosen is the 8th grade pupils which selected randomly. One class as experiment class, and the other is controlled class. The result of the research is obtained from mathematical generalization skill test instrument of phytagoras and self-concept skill inquiry as non-test instrument. Mathematical generalization skill post-test result and final inquiry are analyzed by using Spearman to find the correlation. The result shows that there is a correlation between mathematical generalization skill and student’s self-concept in learning mathematics.